Epilogue - Drent, R.H. (ARCTIC, 1991)
Although the papers presented here do not have the pretension of exhaustively reviewing the adaptations enabling survival through the polar winter, the range of organisms covered nevertheless allows one to discern recurring themes. For the endotherms it is tempting to set the current views against the background of the generalizations arrived at by Scholander and his co-workers . in their key papers cited repeatedly during the Life of the Polar Winter conference. . We can ask why the paradigm of Newtonian cooling advanced at that time has been such a successful approach to the problem of cold adaptation and to what extent the conclusions based on the wide-ranging survey undertaken then are still valid today. . The basic tenet of the Scholander view was that adaptation to arctic life primarily entailed the acquisition (or perfection) of effective insulation, thus allowing cold exposure without excessive costs. . The vivid accounts of ongoing research presented during the symposium and in this issue underline the shifting emphasis away from relatively short-term incursions to the arctic environment to capture specimens for subsequent study towards long-term work by teams of investigators following individual animals over long periods (maintaining contact by an impressive array of telemetric devices). The challenge of the years ahead will be to trace the web of adaptation through the food chain by close collaboration among specialists. In the case of herbivory, cooperation between botanists and zoologists alluded to by Sonesson has already revealed the intimate links connecting animal numbers with their food supply and especially with the persistence of the preferred vegetation . The close fit between the overall standing crop of vegetation and peak reindeer biomass across a range of arctic sites, even extrapolating to an accurate prediction of the carrying capacity of the sub-Antarctic island South Georgia, argues for the pervasive influence of food supply as against the traditional interpretation of populations ...